Neighbourhood Satisfaction and Density Perception in Indian Cities of Bhopal and Nagpur (International Journal of Built Environment and Sustainability, 2025)
Density is an important urban form component. It is a tool that has been used for guiding the way cities are planned for living. Indian cities have been following high-density living, but some researchers showcase that high-density has negative effects. An investigation is necessary to verify the crowding effect and NH sustainability. The paper aims to find if residents are satisfied with the high-density living in the Indian cities of Bhopal and Nagpur. The study identifies context-specific NH satisfaction indicators using Analytical Hierarchy Process (AHP). Based on indicators, data is collected from differing density neighbourhoods. It uses Descriptive as well as Inferential analysis to arrive at results. Further, sensitivity analysis is made using Aggregated Index (AI). Descriptive analysis found a trend of density variation as per each indicator. Inferential statistics (MANOVA) confirms that public perception about density mostly differs in NHs of varying density. The results show that high density proves to be sustainable for variables like NH quality, Community wellbeing and Social equity.The study discusses certain NH interventions that can be useful in deriving future NH design guidelines and framing housing policies in India. Neighbourhood (NH) satisfaction assessment can comment upon the sustainability in a NH. The method can be a starting point to test the sustainability NHs for Indian cities.
Keywords: Sustainability; Satisfaction; High-density; Perceived density; Neighbourhood (NH).